Private health insurance coverage-related lawsuits - Ana Beatriz Perez Afonso; Mayra Gonçalves Menegueti; Thamiris Ricci de Araújo; Lucieli Dias Pedreschi Chaves; Ana Maria Laus
ABSTRACT Objectives: to analyze lawsuits brought by beneficiaries of health insurance operators. Methods: this was a cross-sectional descriptive study carried out in a large-capacity private health insurance operator using data collected by the company from 2012 to 2015. Results: ninety-six lawsuits were brought by 86 beneficiaries regarding medical procedures (38.5%), treatments (26.1%), examinations (14.6%), medications (9.4%), home care (6.2%), and other types of hospitalization (5.2%). The procedures with the highest number of lawsuits were percutaneous rhizotomy; chemotherapy; treatment-related positron-emission tomography scans; and for medications relative to antineoplastic and Hepatitis C treatment. Conclusions: the lawsuits were filed because of the operators' refusal to comply with items not established in contracts or not regulated and authorized by the Brazilian National Regulatory Agency for Private Health Insurance and Plans, refusals considered unfounded.